Pengaruh Budaya Organisasi Terhadap Kualitas Pelayanan Di Dinas Tenaga Kerja Dan Transmigrasi Kabupaten Gowa - Hamsiah, ST; Malik, Ihyani; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2022)
This study purposed to find out the influence of organizational culture on service quality at the Manpower and Transmigration Office of Gowa Regency. This study used the method. Data collection techniques used a questionnaire in the form of a checklist and documentation. The data were analyzed by using descriptive statistics with a simple linear regression formula. The data was explained in the form of tables, frequency and narrative of the processed data with SPSS. The results showed that the influence of organizational culture on service quality at the Manpower and Transmigration Office of Gowa Regency was very significant, namely the effect of self-awareness (X1) on service quality (Y) of 0.102 or 10.2%, the effect of aggressiveness (X2) on quality. service (Y) was 0.069 or 6.9%, the influence of personality (X3) on service quality (Y) was 0.027 or 27%, the effect of performance (X4) on service quality (Y) was 0.290 or 29%, and the influence of team orientation (X5) on service quality (Y) of 0.243 or 24.3% which indicated that organizational culture affects service quality and also influenced by other variables that had not been examined in this study. Therefore, the hypothesis in the study was accepted because it was supported by a significance value.Keywords: Influence, Organizational Culture, Public Service